Pengaruh Kepemimpinan Kepala Madrasah terhadap Profesionalisme Guru dalam Membimbing Siswa di MIN 2 Pekanbaru - Muhammad Azroi; Deprizon (PT. Penerbit Tiga Mutiara, 2025)
This study aims to comprehensively examine the influence of the madrasah principal’s leadership on teacher professionalism in guiding students at MIN 2 Pekanbaru, positioning educational leadership as a key element that determines the quality of pedagogical practice. The investigation focuses on three main questions, namely the characteristics of the principal’s leadership, the level of teacher professionalism, and the extent to which leadership contributes to the effectiveness of student guidance. The novelty of this research lies in the integration of instructional, managerial, and entrepreneurial leadership concepts with teachers’ pedagogical and professional competencies, resulting in a more holistic understanding of the mechanisms through which leadership influences the guidance process that requires accuracy in planning, precision in implementation, and rigor in evaluation. The findings reveal a positive and significant relationship between the principal’s leadership and teacher professionalism, with a contribution of 61.1%, indicating that the majority of improvements in teacher professionalism are shaped by the quality of leadership practiced. Supportive and participatory leadership, reinforced by continuous academic supervision, is proven to enhance teachers’ capacities, strengthen work motivation, and create a professional environment conducive to effective student guidance. These outcomes demonstrate that the effectiveness of guidance is not solely influenced by individual teacher competence but also by leadership structures that direct, facilitate, and optimize educator performance systematically. This study concludes that the madrasah principal holds a central role as a driver of improved guidance quality through the application of visionary, adaptive, and human-resource-oriented leadership, whose implications may serve as a basis for formulating strategies to enhance teacher competence and strengthen educational leadership models within madrasah institutions.